Characterization and Typology Analysis of Cattle Breeding Practices on Rural Farms in Northern Côte d’Ivoire - Yao, F. A. D.; N’Goran, K. E.; Ekra, J.-Y.; Kanh, K. H. M.; Tre, U. B.; Konaté, A.; Sonan, H.; Diloreto, E.; Mafie, E. M. (Tropical Animal Science Journal, 2025)
A comprehensive understanding of agricultural production variables is essential for developing effective agricultural strategies. To identify the key factors shaping cattle farming practices in Côte d’Ivoire, a study was conducted to characterize the diversity of livestock farming practices and identify the different typologies of livestock production systems in the northern (Poro, Tchologo, and Bagoué) and north-eastern (Bounkani) regions. The methodology involved a structured survey targeting livestock farmers. Participants were selected based on two main criteria: the accessibility of their farms and their willingness to share information. Data collection was carried out using a standardized questionnaire designed to gather information on socio-economic characteristics, herd composition, farming practices, and constraints. Of the 105 livestock farmers initially identified, only 53 satisfied the inclusion criteria and were included in the survey. The results revealed that cattle farming is predominantly managed by Peulh ethnic groups originating from neighbouring countries (Mali and Burkina Faso) to the north. Herds are largely composed of Méré and Zebu cattle breeds. Through data analysis, three distinct livestock production systems were identified: (i) sedentary native farmers engaged in livestock rearing as a secondary activity alongside trade, (ii) semi-transhumant Fulani pastoralists for whom livestock is the primary livelihood, and (iii) agro-pastoralists integrating crop and livestock farming. The main challenges reported by farmers include feed shortages and animal diseases, with additional constraints related to land-use conflicts and limited access to agricultural services. Farmers expressed the need for designated grazing areas, affordable feed supplements, and improved access to veterinary care. This typology provides a clear view of livestock systems in Côte d’Ivoire. It serves as an effective foundation for an integrated strategy to improve Ivorian livestock production.